2011
DOI: 10.1007/s10791-011-9167-7
|View full text |Cite
|
Sign up to set email alerts
|

Intent-based diversification of web search results: metrics and algorithms

Abstract: We study the problem of web search result diversification in the case where intent based relevance scores are available. A diversified search result will hopefully satisfy the information need of user-L.s who may have different intents. In this context, we first analyze the properties of an intent-based metric, ERR-IA, to measure relevance and diversity altogether. We argue that this is a better metric than some previously proposed intent aware metrics and show that it has a better correlation with abandonment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 21 publications
0
79
0
Order By: Relevance
“…Table 4 provides some information on the evaluation measures that were used in the present study. For the adhoc/news and adhoc/web tasks, we consider the binary Average Precision (AP), Q-measure (Q) (Sakai 2005), normalised Discounted Cumulative Gain (nDCG) (Järvelin and Kekäläinen 2002) and normalised Expected Reciprocal Rank (nERR) (Chapelle et al 2011), all computed using the NTCIREVAL toolkit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 provides some information on the evaluation measures that were used in the present study. For the adhoc/news and adhoc/web tasks, we consider the binary Average Precision (AP), Q-measure (Q) (Sakai 2005), normalised Discounted Cumulative Gain (nDCG) (Järvelin and Kekäläinen 2002) and normalised Expected Reciprocal Rank (nERR) (Chapelle et al 2011), all computed using the NTCIREVAL toolkit.…”
Section: Methodsmentioning
confidence: 99%
“…For the diversity/web task, we consider a-nDCG (Clarke et al 2009) and Intent-Aware nERR (nERR-IA) (Chapelle et al 2011) computed using ndeval, 28 as well as D-nDCG and D]-nDCG (Sakai and Song 2011) computed using NTCIREVAL. When using NTCIREVAL, the gain value for each LX-relevant document was set to gðrÞ ¼ 2 x À 1: for example, the gain for an L3-relevant document is 7, while that for an L1-relevant document is 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is a shame that such expensive collections are not reusable, although we have shown that condensed-list metrics may provide more accurate results for non-contributors than traditional metrics. Given this situation, one useful future direction for diversity evaluation would be to establish a metholodogy for efficient and economical construction of disposable diversity test collections: instead of explicitly defining a set of possible intents for each topic a priori 5 , would it be possible to automatically extract implicit intents from a given set of systems and rank them by "relative diversity"? Would the relative diversity correlate well with the users' diversity preferences?…”
Section: Discussionmentioning
confidence: 99%
“…Clarke et al [9] and Chapelle et al [5] have independently described α-nDCG and ERR-IA in a single framework. What distinguishes α-nDCG and ERR-IA from other diversity metrics is their per-intent diminishing return property [5]: every time a document relevant to an intent is found, the value of the next document found that is relevant to the same intent is discounted. Thus these metrics penalise redundant information for each intent, and thereby encourages diversity across intents.…”
Section: Diversity Evaluation Metricsmentioning
confidence: 99%
“…Rafiei et al [12] modeled the diversity problem as expectation maximization and presented algorithms to estimate the optimization parameters. In [4], documents are selected sequentially according to relevance. The relevance is conditioned on documents having been already selected.…”
Section: Introductionmentioning
confidence: 99%